Early ischaemic and haemorrhagic complications after atrial fibrillation-related ischaemic stroke: analysis of the IAC study. Issue 7 (13th May 2020) - Yaghi, Shadi; Henninger, Nils; Scher, Erica; Giles, James; Liu, Angela; Nagy, Muhammad; Kaushal, Ashutosh; Azher, Idrees; Mac Grory, Brian; Fakhri, Hiba; Espaillat, Kiersten Brown; Asad, Syed Daniyal; et al.
Abstract : Introduction: Predictors of long-term ischaemic and haemorrhagic complications in atrial fibrillation (AF) have been studied, but there are limited data on predictors of early ischaemic and haemorrhagic complications after AF-associated ischaemic stroke. We sought to determine these predictors. Methods: The Initiation of Anticoagulation after Cardioembolic stroke study is a multicentre retrospective study across that pooled data from consecutive patients with ischaemic stroke in the setting of AF from stroke registries across eight comprehensive stroke centres in the USA. The coprimary outcomes were recurrent ischaemic event (stroke/TIA/systemic arterial embolism) and delayed symptomatic intracranial haemorrhage (d-sICH) within 90 days. We performed univariate analyses and Cox regression analyses including important predictors on univariate analyses to determine independent predictors of early ischaemic events (stroke/TIA/systemic embolism) and d-sICH. Results: Out of 2084 patients, 1520 patients qualified; 104 patients (6.8%) had recurrent ischaemic events and 23 patients (1.5%) had d-sICH within 90 days from the index event. In Cox regression models, factors associated with a trend for recurrent ischaemic events were prior stroke or transient ischemic attack (TIA) (HR 1.42, 95% CI 0.96 to 2.10) and ipsilateral arterial stenosis with 50%–99% narrowing (HR 1.54, 95% CI 0.98 to 2.43). Those associated with sICH were male sex (HR 2.68, 95% CI 1.06 to 6.83), history of hyperlipidaemia (HR 2.91, 95% CI 1.08 to 7.84) and early haemorrhagic transformation (HR 5.35, 95% CI 2.22 to 12.92). Conclusion: In patients with ischaemic stroke and AF, predictors of d-sICH are different than those of recurrent ischaemic events; therefore, recognising these predictors may help inform early stroke versus d-sICH prevention strategies.